Witches' broom of Acacia auriculiformis and its phytoplasmal etiology - and M. KRISHNAREDDY, H. PRADEEP KUMAR, V. SURYANARAYANA*, R.P. PANT, MUKESH SRIVASTAVA (Indian Phytopathology, 2007)
Witches' broom disease of Acacia auriculiformis an evergreen plantation species was observed in Uttara Kannada district of central Western Ghat part of Karnataka. The incidence of disease ranged from 0.11 to 0.20%. Infected trees exhibited mild chlorosis, elongated narrowed leaves, excessive proliferated shoots, bushiness, upright growth habit and tree mortality. Transmission through grafting, dodder and rooting of stem cuttings treated with growth regulators was not successful. Tetracycline application has induced a temporary remission of symptoms. Pleomorphic bodies of varied sizes in the phloem tissues of ultra thin sections of infected trees were observed under Electron microscopy indicating the phytoplasmal etiology.